SYNTHESIS OF SILVER NANOPARTICLES IN POLYMER MATRICES BY GAMMA RADIATION - Cabrera, Julieta (2008)
Silver nanoparticles have been obtained by gamma radiation from aqueous solutions of AgNO3 in the presence of polyvinylpyrrolidone (PVP) or poly(vinyl alcohol) (PVA). The size and forms of nanoparticles, analyzed by electronic microscopy of transmission, are strongly influenced by the type of polymer as well as of its concentration. The size of nanoparticles obtained using PVP oscillate around 10 to 50 nm, with a narrow distribution of particles size for the majority of cases. The morphology of these nanoparticles, spherical or hexagonal, depends of PVP concentration. A similar case was observed When PVA was used as stabilizer. Silver nanorods, 2.5 µm long, were observed for PVA 1% aqueous solution. Accordingly to the diffraction analyses of electrons the silver nanorods are contaminated with Ag2O. The UV-Visible spectra show absorption bands of the superficial plasmon between 406 and 453 nm.